The effect of irrigation solutions and sterilization process on the surface properties of ProTaper Next and TruNatomy rotary files: An atomic force microscopy study - Öztekin, Faruk; Elmalı, Enes (My University, 2022)
Aim: This study sought to evaluate the effects of different irrigation solutions and sterilization processes on the surface properties of ProTaper Next (PTN; Dentsply-Maillefer, Ballaigues, Switzerland) and TruNatomy (TN; Dentsply Sirona, Ballaigues, Switzerland) nickel-titanium rotary files. Methodology: 30 ProTaper Next and 30 TruNatomy files were used. Both types of files were divided into five groups. The files in three groups were dipped into 5.25% NaOCI (CanalPro, Coltene/Whaledent, Altstätten, Switzerland), BioAKT (New Tech Solutions s.r.l., Brescia, Italy), and 18% etidronic acid (Dual Rinse HEDP, Medcem, Weinfelden, Switzerland), respectively, for 5 minutes, while the files in the fourth group were exposed to five autoclave cycles. The files in the fifth (control) group did not receive any treatment. Scans were performed from five different points using an atomic force microscope (AFM). The assumption of the conformity of the quantitative variables to a normal distribution was evaluated using the Kolmogorov-Smirnov test. A one-way analysis of variance was used to compare the quantitative measures between more than two independent groups, while the post-hoc least significant difference test was used for the pairwise comparisons (p?0.05). Results: AFM images of the PTN and TN files in all the groups revealed surface irregularities. The root mean square (RMS) and depth values of the files dipped in NaOCI, BioAKT, and Etidronic acid were statistically higher than those of the control group (p<0.05). Moreover, the RMS and depth values were statistically higher in the files that had been subjected to five autoclave cycles when compared with the control group (p<0.05). The RMS values and depth values among the groups were found to be compatible. Conclusion: All the applications increased the surface roughness of the PTN and TN files. The Etidronic acid and sterilization applications were found to increase the RMS and depth values the most when compared with the control group.
Keywords: Diş Hekimliği